2017
DOI: 10.1159/000485783
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Promotes the Survival and Adipogenesis of Ischemia-Challenged Adipose Derived Stem Cells by Improving Autophagy

Abstract: Background/Aims: Ischemia is one of the main causes of the high rate of absorption of transplanted autologous fat. Autophagy allows cells to survive by providing energy under starvation. Rapamycin has been found to play a role in promoting autophagy. In this study, we investigated whether rapamycin participates in the survival and adipogenesis of ischemia-challenged adipose-derived stem cells (ADSCs) by regulating autophagy. Methods: Before the cells were exposed to oxygen-glucose deprivation (OGD), a simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…3a, b). And we examined the influence of rapamycin (a well-documented autophagy inducer) on the number of autophagosomes and autolysosomes [28]. Our results demonstrated that the numbers of yellow puncta (early autophagosomes) were higher in the rapamycin treated group than the control group (2.0±0.5774 vs 6.667±0.8819, P < 0.05 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a, b). And we examined the influence of rapamycin (a well-documented autophagy inducer) on the number of autophagosomes and autolysosomes [28]. Our results demonstrated that the numbers of yellow puncta (early autophagosomes) were higher in the rapamycin treated group than the control group (2.0±0.5774 vs 6.667±0.8819, P < 0.05 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the cells were able to maintain their viability for several days despite the complete exhaustion of glucose. This could possibly be due to an enhanced autophagic activity of the cells, as autophagy has been shown to be a survival mechanism for oxygen/glucose-deprived MSCs [ 36 , 37 , 38 ]. A further observation was that those ASCs that survived under the harsh ischemic condition (glucose/oxygen deprivation) were not affected in their adipogenic differentiation capability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggests that short-term, but not long-term, inhibition of the mammalian target of rapamycin (mTOR) activity intensifies mesenchymal stem cell immunomodulation. In BMSCs, short-term Rapa results in elevated production of immune-modifying factors increased immunosuppression of PBMC or splenocyte proliferation, and protection against apoptosis following exposure to ischemia or oxygen-glucose deprivation [ 28 , 51 ]. In the present study, we examined the effect of short-term mTOR inhibition with Rapamycin on the immunomodulatory capacity of ASCs in the EAE mouse model of MS. Our results demonstrate that control ASCs exhibited significant therapeutic benefits when administered at DPI 20, as indicated by improved clinical scores, modestly better rotarod performance, and increased myelin levels in the lumbar spinal cord compared to vehicle-treated EAE mice.…”
Section: Discussionmentioning
confidence: 99%
“…The preconditioning of MSCs with Rapa results in substantial improvement of their immunoregulatory function in animal models of graft vs. host disease and cutaneous wound healing [ 23 , 24 ]. Moreover, Rapa exposure has demonstrated an effective reversal of MSC senescence [ 25 , 26 , 27 ], resiliency to apoptosis-inducing stimuli [ 28 ], and robust enrichment of immunomodulatory function [ 29 , 30 , 31 ]. Furthermore, short-term Rapa exposure caused an increase in both cyclooxygenase-2 (COX2) and prostaglandin-E2 (PGE2) in bone marrow-derived mesenchymal stem cells (BMSCs) in vitro [ 30 ].…”
Section: Introductionmentioning
confidence: 99%